Some hormonal, lipid and haemodynamic maintenances of alternative vegetotropic effects of balneotherapy on SPA Truskavets’ - Flyunt, Igor-Severyn S; Musiyenko, Vira Y; Horkovenko, Nataliya L; Fil’, Vitaliy M; Ivassivka, Anzhela S; Zukow, Walery (Journal of Education, Health and Sport, 2017)
Background.The data on the influence of balneotherapy in the spa Truskavets’ on the autonomic nervous system are ambiguous, so research in this direction remains relevant. The purpose of this study is accompanying changes in some hormonal, lipid and hemodynamic parameters in women with alternative variants of the vegetotropic effect of balneotherapy. Materials and Methods. The object of the study were 30 women aged 30-50 years old, patients with chronic cholecystitis in the remission phase, combined with polycystic ovaries and hyperplasia of the thyroid gland. Before and after balneotherapy, HRV was recorded and hormonal, lipid as well as veloergometric parameters were determined.Results. We confirmed the ambivalent nature of the vegetotropic effect of balneotherapy:sympathicotonic in 57% women and vagotonic in 43%. It is revealed the tendency to decrease testosterone level with sympathicotonic effect and the opposite tendency with vagotonic effect. There were no significant differences with respect to thyroid hormones, FSH, estradiol, prolactin and cortisol. Vagotonic but not sympathicotonic effect is accompanied by a tendency to decrease the coefficient of atherogenicity and the response of systolic blood pressure to standard physical load. Conclusion. Alternative vegetotropic effects of balneotherapy on spa Truskavets’ are accompanied by alternative changes in the level of testosterone alone, but no other registered hormones as well as lipid and hemodynamic parameters.